Study on Exchange of Radioactive Bromide Ion on Duolite A-162 Resin - LOKHANDE, R.S.; KARTHIKEYAN, PRETTY (Asian Journal of Chemistry, 2010)
The kinetics of ion exchange reaction has been studied by application of 82Br as tracer isotope. The exchange rates of ion exchange resin Duolite A-162 have been determined. Kinetics of ion exchange at different temperatures ranging from 27 to 50oC and particularly at low concentration of electrolyte (KBr) ranging from 0.005 to 0.100 M and for different amount of ion exchange resin ,ranging from 1 to 5 g is carried out